An Analysis of USSFeed’s Caption on Instagram Based on the Logical Atomism Concept - Silfa Dzukhriyah; Setia Rini (Journal of English Education and Linguistics, 2022)
The purpose of this paper is to analyze language using Bertrand Russell's logical atomism concept. In this article, Russell's concept of logical atomism is also discussed. According to Russell, logical atomism maintains that language may be separated into atomic propositions and compound propositions when talking about words and language as a means of conveying information. Research was conducted using both qualitative and library-based techniques. The data utilized was taken from an Instagram post by the USSFeeds account, which disseminates the most recent news for everyone from youngsters to adults with a focus on the international market. The researcher then analyzes it in terms of Russell's atomic propositions of logical atomism. Logical atomism is an ideology that holds that language may be divided into atomic propositions and compound propositions when discussing words and language as a carrier of information. Additionally, by adding the terms "and", “who”, “that” “or”, and etc these atomic assertions may be combined to make compound propositions. USSFeed captions that are analyzed using the concept of logical atomism must be added with conjunctions to clarify the intended reference. Keywords: Logical atomism, Bertrand Russell, USSFeed.